Prediction of forex trend movement using linear regression line, two-stage of multi-layer perceptron and dynamic time warping algorithms - Tiong, Leslie Ching Ow *; Ngo, David Chek Ling *; Lee, Yunli * (Universiti Utara Malaysia, 2016)
Foreign Exchange Currency prediction has become a challenging task since the late 1970s due to uncertainty movement of exchange rates. However, most researchers in this area were neglecting to analyse trend patterns from historical Forex data as input features. Thus, this motivates us to investigate possibility of repeated trend patterns from historical Forex data. This paper aims to investigate the repeated trend patterns as features from historical Forex data, which proposes new combination techniques - Linear Regression Line, two-stage of Multi-Layer Perceptron and Dynamic Time Warping algorithms in order to improve the performance of prediction significantly, thus achieving greater accuracy.